A Meta-Analysis of the Impact of Anaerobic Soil Disinfestation on Pest Suppression and Yield of Horticultural Crops - Shrestha, Utsala; Augé, Robert M.; Butler, David M. (Frontiers in Plant Science, 2016)
Anaerobic soil disinfestation (ASD) is a proven but relatively new strategy to control soil borne pests of horticultural crops through anaerobic decomposition of organic soil amendments. The ASD technique has primarily been used to control soil borne pathogens; however, this technique has also shown potential to control plant parasitic nematodes and weeds. ASD can utilize a broad range of carbon (C) amendments and optimization may improve efficacy across environments. In this context, a meta-analysis using a random-effects model was conducted to determine effect sizes of the ASD effect on soil borne pathogens (533 studies), plant parasitic nematodes (91 studies), and weeds (88 studies) compared with unamended controls. Yield response to ASD was evaluated (123 studies) compared to unamended and fumigated controls. We also examined moderator variables for environmental conditions and amendments to explore the impact of these moderators on ASD effectiveness on pests and yield. Across all pathogen types with the exception of Sclerotinia spp., ASD studies show suppression of bacterial, oomycete and fungal pathogens (59% to 86%). Pathogen suppression was effective under all environmental conditions (50% to 94%) and amendment types (53% to 98%), except when amendments applied at rates less than 0.3 kg m-2. The ASD effect ranged from 15% to 56% for nematode suppression and 32% to 81% for weed suppression, but these differences were not significant. Significant nematode moderators included study type, soil type, sampling depth, incubation period, and use of mixed amendments. Weed suppression due to ASD showed significant heterogeneity for all environmental conditions, confirming that these studies do not share a common effect size. Total crop yield was not reduced by ASD when compared to a fumigant control and yield was significantly higher (30%) compared to an unamended control, suggesting ASD as a feasible option to maintain yield without chemical soil fumigants. We conclude ASD is effective against soil borne pathogens and while not conclusive due to a limited number of studies, we expect the same for nematodes and weeds given observed effect sizes. Findings should assist researchers in exploring ASD efficacy in particular environmental conditions and allow for development of standard treatment protocols.